Energy system analysis of Volvo Penta’s micro grid with optimized battery storage - Sjölander, Jonathan (My University, 2024)
Abstract This thesis investigates the integration of battery storage solutions within marine micro grid environments, focusing on the Krossholmen test site operated by Volvo Penta. A systematic literature review employing integrative and meta-analysis approaches establishes the theoretical foundation, covering topics such as linear optimization, energy-systems modeling, and future energy scenarios. Detailed descriptions of the Krossholmen micro grids technical specifications, including demand profiles and energy system components, are documented to facilitate accurate modeling.Future energy scenarios, reflecting variations in electricity markets and renewable energy adoption, are developed to assess the effectiveness of battery energy storage solutions under different conditions. Linear optimization techniques, implemented through Python-based modeling modules, are utilized to determine the optimal operation of the micro grid. A minimize-cost objective function, incorporating various constraints, guides the modeling process, with provisions to incorporate non-linear data, such as battery degradation, in later stages. The project encompasses seven major milestones, each aligned with specific deliverables, ensuring the project’s successful execution within the allocated timeframe. Through this comprehensive approach, the thesis contributes to advancing understanding and practical applications of battery storage within marine micro grid contexts.
Keywords: Keywords: Microgrid, Energy Storage, Solar PV, Wind turbines, Electrification, Electrical motor boats, Test site